Renin–angiotensin system antagonists in the perioperative setting: clinical consequences and recommendations for practice. Issue 1029 (25th March 2011) - Auron, Moises; Harte, Brian; Kumar, Ajay; Michota, Franklin
Abstract : There are no existing guidelines supporting the withdrawal or continuation of renin–angiotensin–aldosterone system (RAAS) antagonists in the preoperative setting. RAAS antagonists include ACE inhibitors, angiotensin II receptor subtype 1 blockers and direct renin inhibitors (eg, aliskiren), as well as the aldosterone antagonists. The use of these agents before surgery has been associated with a variable incidence of hypotension during the initial 30 min after induction of anaesthesia; however, these hypotensive episodes have not been conclusively linked to any significant postoperative complications, although recent data suggest an increase in postoperative morbidity and mortality in patients undergoing coronary artery bypass grafting. Further studies are required to be able to demonstrate if the organ-protective benefits of RAAS antagonists justify their continuation in the perioperative setting. Temporary withdrawal of RAAS antagonists in these patients may prevent or attenuate intraoperative hypotension and hypovolaemia. Alternatively, the increase in RAAS activity and blood pressure expected with cessation of RAAS antagonist therapy may impair regional circulation secondary to an increase in systemic vascular resistance. Full discussion of the potential implications of perioperative RAAS antagonist therapy with the surgical team is important, and strategies to ensure careful monitoring and maintenance of adequate intravenous volume before induction of anaesthesia are essential.